Conditionally Essential Amino Acid Supplementation Reduces Postoperative Complications and Muscle Wasting After Fracture Fixation: A Randomized Controlled Trial. (14th March 2022) - Hendrickson, Nathan R.; Davison, John; Glass, Natalie A.; Wilson, Erin S.; Miller, Aspen; Leary, Steven; Lorentzen, William; Karam, Matthew D.; Hogue, Matthew; Marsh, J. Lawrence; Willey, Michael C.
Abstract : Background: Postoperative complications and substantial loss of physical function are common after musculoskeletal trauma. We conducted a prospective randomized controlled trial to assess the impact of conditionally essential amino acid (CEAA) supplementation on complications and skeletal muscle mass in adults after operative fixation of acute fractures. Methods: Adults who sustained pelvic and extremity fractures that were indicated for operative fixation at a level-I trauma center were enrolled. The subjects were stratified based on injury characteristics (open fractures and/or polytrauma, fragility fractures, isolated injuries) and randomized to standard nutrition (control group) or oral CEAA supplementation twice daily for 2 weeks. Body composition (fat-free mass [FFM]) was measured at baseline and at 6 and 12 weeks postoperatively. Complications were prospectively collected. An intention-to-treat analysis was performed. The relative risk (RR) of complications for the control group relative to the CEAA group was determined, and linear mixed-effects models were used to model the relationship between CEAA supplementation and changes in FFM. Results: Four hundred subjects (control group: 200; CEAA group: 200) were enrolled. The CEAA group had significantly lower overall complications than the control group (30.5% vs. 43.8%; adjusted RR = 0.71; 95% confidence interval [CI] = 0.55 to 0.92; p = 0.008). The FFM decreased significantly at 6 weeks in the control subjects (–0.9 kg, p = 0.0205), whereas the FFM was maintained at 6 weeks in the CEAA subjects (−0.33 kg, p = 0.3606). This difference in FFM was not seen at subsequent time points. Conclusions: Our results indicate that CEAA supplementation has a protective effect against common complications and early skeletal muscle wasting after operative fixation of extremity and pelvic fractures. Given the potential benefits of this inexpensive, low-risk intervention, multicenter prospective studies in focused trauma populations are warranted. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.